Treatment of elderly patients with acute myeloid leukemia: personal experience - L. T. Shimanovskaya; E. N. Misyurina; E. A. Baryakh; E. I. Zhelnova; K. V. Yatskov; T. S. Chudnova; T. N. Tolstykh; D. E. Gagloeva (Онкогематология, 2024)
Background. Acute myeloid leukemia (AML) is an aggressive malignancy of the hematopoietic system. Most patients with newly diagnosed AML are 65 years of age or older. Treatment of this cohort of patients is difficult due to the comorbidity of elderly patients and the genetic characteristics of hemoblastosis, which prevents the achievement of significant progress in treatment, in contrast to younger patients with AML. As domestic and foreign studies have shown, age is an independent universal prognosis factor for AML. In the era of targeted drugs, successful treatment of AML is becoming possible.Aim. To assess overall survival in elderly patients with AML, tolerability and effectiveness of various treatment regimens in patients with AML ≥65 years.Materials and methods. This paper presents our own experience in the treatment of elderly patients with AML in the hematology departments of the City Clinical Hospital No. 52. The study included patients over 65 years of age with AML from April 2022 to September 2023. A total of 40 patients were analyzed. To determine the risk factors for death, univariate and multivariate regression analyzes were performed using the logistic regression method. Variables that showed statistical significance on univariate analysis were included in the multivariate analysis. An analysis of 12‑month overall survival was also carried out using the Kaplan–Meier method with the construction of survival curves and calculation of median survival. A comparative analysis of two groups of patients treated with the AZA + EN and LdaraC regimens was carried out.Results. 63 % (n = 25) are men, 37 % (n = 15) are women. The median age was 75 years; all patients had complicated premorbid background. 53 % (n = 21) of patients were in the age range from 65 to 69 years, 47 % (n = 19) were over 70. Antitumor treatment was received by 88 % (n = 35) of patients. The remaining 5 underwent: best accompanying (n = 2), cytoreductive (early death at this stage) (n = 3) therapy. Complete remission after two cycles of therapy was achieved in 46 % (n = 16) of patients, and in 29 % (n = 10) it was maintained at the time of analysis. Early relapse occurred in 14 % (n = 5). Early mortality was recorded in 9 % (n = 3). Death was reported in 40 % (n = 16) of patients. 20 % (n = 7) of patients were refractory to first-line therapy, of which 36 % (n = 5) were treated with low doses of cytarabine (LdaraC), the rest to a combination of azacitidine (AZA) with venetoclax (EN). The number of relapses among patients on AZA + EN and LdaraC therapy was comparable.Conclusion. AZA + EN is the first-line treatment of choice in older patients with AML. The possibility of conducting this course in an outpatient setting makes it most convenient for both hematologists and patients. An important aspect in the treatment of AML in elderly patients is improving and maintaining quality of life.